The relationship of physical balance and energy value in sheep rations. - Bell, T.D.; Cox, R.F.; Hughes, J.S. (Kansas Agricultural Experiment Station, 2012)
Lamb fattening rations varying in physical nature but virtually alike chemically have been studied at the Kansas Agricultural Experiment Station for a number of years. Previous tests have been demonstrated that the rate of gains and the efficiency of feed utilization by fattening lambs are associated closely with the physical balance or the concentration and bulkiness of the ration.
Keywords: Sheep; Energy value; Gain; Efficiency